Does it take the joints to stretch a mind? The ADHD and General Joint Hypermobility connection - Julia Kacperczyk; Witold Czyż; Michalina Wójcikiewicz; Filip Arczewski; Karol Dziedzic; Julia Kulbacka; Maciej Wojszczyk; Damian Zys; Piotr Pasek; Julia Ryniecka (Quality in Sport)
Attention-deficit/hyperactivity disorder (ADHD) is a childhood-onset neurodevelopmental disorder characterized by symptoms of inattention, hyperactivity-impulsivity, or both, which negatively affect the quality of life for children and adults worldwide. ADHD is known to cause significant psychosocial distress, including academic failure, divorce, unemployment, and incarceration, and increases the risk of developing psychiatric disorders such as depression, anxiety, and substance abuse.